The Impact of Digital Transformation and Entrepreneurial Orientation on Women-Led MSME Performance: The Mediating Role of Innovation Capability - Engel San Andrea; Patricia (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a central role in Indonesia’s economy by generating employment and contributing to GDP. However, rapid technological change requires MSMEs to embrace digital transformation and strengthen entrepreneurial orientation to sustain growth. This study investigates how digital transformation and entrepreneurial orientation affect MSME performance, with innovation capability serving as a mediating factor. A quantitative descriptive design was employed, collecting data through surveys from 150 women-led MSMEs in the Greater Jakarta area. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test seven proposed hypotheses. The results indicate that digital transformation and entrepreneurial orientation both have positive effects on innovation capability and business performance. Furthermore, innovation capability significantly improves MSME performance and mediates the influence of digital and entrepreneurial factors. This study contributes to the literature by linking digital transformation and entrepreneurial orientation with innovation-driven performance in women-led MSMEs. It also provides practical insights for policymakers and support institutions to develop digitalization and innovation programs that strengthen competitiveness in a dynamic market environment.